2019
DOI: 10.18203/2349-3291.ijcp20190700
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoepidemiology, clinical profile and outcome of venomous snake bite in children in Konaseema region of Andhra Pradesh, India

Abstract: Background: Venomous snake bite is an acute medical emergency, and children are more quickly and severely affected than adult. Venomous snake bite is responsible for 28.5 deaths per 1000 snake bite death among 5-15years old children. Most of them used to be from rural India and is more common in school going children. But there is no study regarding clinic epidemiology and treatment outcome among pediatric age group in this part of Andhra Pradesh. This retrospective descriptive has been conducted to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…With respect to time of bite 38 (48.72%) participants reported evening time of bite. These results are similar to other studies which gives an idea about the behaviour of snakes and expected interaction with humans [13,14]. In our study we analysed the seasonality of snake bite.…”
Section: Resultssupporting
confidence: 91%
“…With respect to time of bite 38 (48.72%) participants reported evening time of bite. These results are similar to other studies which gives an idea about the behaviour of snakes and expected interaction with humans [13,14]. In our study we analysed the seasonality of snake bite.…”
Section: Resultssupporting
confidence: 91%
“…In our study, it was observed that lower limbs were the site of snake bite in 126 (78.8%) children. This finding is a consistent feature seen in all studies done in children [5][6][7][8][9] . We would suggest that use of protective footwear and clothes would help in reducing the risk of snake bite envenomation.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that children in the age group of 6-15 years were more prone for snake bite. Kumar AH, et al 6 , Rao KV, et al 9 found similar vulnerability of children of school going age.…”
Section: Discussionmentioning
confidence: 79%
“…A similar type of distribution of envenomation was reported from other parts of the country. [ 2 , 12 ] Though cellulitis was the most common local manifestation (40% and 60%) found in other studies,[ 10 , 13 ] we had a lower incidence of the same.…”
Section: Discussionsupporting
confidence: 43%